Rethinking digital photography : making & using traditional & contemporary photo tools - Neel, John (Photographer) (New York : Pixiq, 2011)
Demonstrates how to create innovative photographs through the use of digital cameras, current software, and such unconventional methods as homemade lenses made with household items or parts from obsolete cameras.
Gadgets and hybrids -- Lens systems -- Alternative lenses -- Macro and pinhole photography -- High dynamic range [HDR] -- Painting the photograph -- Panoramas -- MicroPalnets and mandalas -- Multiple dimensions, multiple media.
Includes index.
Keywords: Photography -- Digital techniques; Digital photography